Pleuropulmonary nocardiosis due to Nocardia otitidiscaviarum in a debilitated host - R Deepa; S Thasneem Banu; G Jayalakshmi; J Durdana Parveen (Wolters Kluwer Medknow Publications, 2016)
Nocardia otitidiscaviarum is a rare cause of pulmonary nocardiosis. We present a case of pulmonary nocardiosis with pleural involvement in an adolescent with rheumatic heart disease and congestive cardiac failure presenting with right lower lobe consolidation and pleural effusion. Direct gram-stain of pleural fluid showed pus cells with Gram-positive filamentous branching bacilli. Empiric treatment with parenteral ceftriaxone and supportive therapy for cardiac failure was initiated. Pleural fluid culture yielded growth of N. otitidiscaviarum at 72 h. Antibiotic susceptibility testing showed resistance to cephalosporins. The patient expired due to congestive cardiac failure on the 5th day.